The doing of the little righteousness – the on-going search for justice after the TRC - Boesak, Allan (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
Taking as point of departure, South African theologian Dirkie Smit’s theological oeuvre, particularly his theological reflections on issues such as politics, justice, peace and reconciliation, the essay moves on to focus on Mahmood Mamdani’s view of the differences between the Nuremberg trials, South Africa’s political negotiations held in Kempton Park and the TRC and his critique of the latter. This once again raises the matter of justice, different forms of justice – especially as either “victor justice” or “survivor justice” and the consequences of this for the TRC and for christians in the call for the doing of justice. With reference to the views of Desmond Tutu (especially his understanding of the concept of ubuntu), it is suggested that the TRC’s only choice was not just between retributive and restorative justice, revenge and forgiveness, but that it was incumbent upon it to advance the gains made at Kempton Park and to move from victim’s justice to survivor’s justice and from the foundation of political justice to social justice which it did not do.